APPLICATION OF ISAK 35 IN THE PRESENTATION OF FINANCIAL REPORTS AT HARISUL KHAIRAT ISLAMIC BOARDING SCHOOL, BUMI HIJRAH, TIDORE ISLANDS - Astri Alim; Kasim Sinen; Mahardika Catur Putriwana Malik (Nusantara Hasana Journal, 2025)
This study aims to analyze the implementation of ISAK 35 in the presentation of financial statements at Pesantren Harisul Khairat Bumi Hijrah Tidore Kepulauan. The type of data used is a qualitative approach with a descriptive-comparative method. The data source used in this research is primary data. Data collection methods applied include field surveys, interviews, and literature studies. Data analysis uses descriptive qualitative analysis. The results of the study show that this organization did not prepare reports in accordance with applicable standards prior to the adoption of appropriate accounting standards. Instead, they only used a manual cash recording system.